Current Use of Uber Brand Marketing Strategy - David Vrtana; Jana Majerova (Communications of International Proceedings, 2020)
There are various factors behind the success of global brands. These factors may include brand strength, competitive advantage, customer loyalty or the proper application of your marketing strategy. In many cases, it must respect the development of current trends. Today's world is characterized by speed, which is largely reflected in the marketing field. People are increasingly demanding on the products and services offered. Their demands on the quality of transport, simplicity, but also on the perception of price differentiation are increasing. The aim of the article is to find out the principles of success of the strategy applied in the company on the basis of relevant information from the given issue. In this article, we focus on the successful use of the marketing strategy of the UBER brand, which was able to change the quality of low-cost travel through a mobile application. We divided the article into three basic parts. In the first part, we analyze the description of the situation that led to the emergence of the service, communication and customer strategy of the brand. We use analysis and synthesis in which we identify different views of authors from various studies focused on the success of marketing strategy. Based on the obtained data, we describe the differentiation strategy and its successful use.
Keywords: UBER; Marketing Strategy; Diferentiation Strategy; Marketing Communication.